Secondary Metabolites of Asclepias curassavica (Apocynaceae) and its Effects on Food Preference and Mortality of Spodoptera frugiperda (Lepidoptera: Noctuidae) - de Leão, Renato Marcos; Cruz, João Vitor Souza; Ramos, Vânia Maria; de Almeida, Viviane Tavares; Gorni, Pedro Henrique; Camargo, Roberto da Silva; Pacheco, Ana Cláudia; Lima, Letícia Vieira de; Forti, Luiz Carlos (Emirates Journal of Food and Agriculture, 2020)
Asclepias curassavica L. plant is toxic for vertebrates, and little is known about its effects on invertebrates, as well as whether its secondary metabolites have an influence on food preference and survival of insects. Thus, a study was conducted to verify the action of A. curassavica on Spodoptera frugiperda J.E.Smith. The plants were collected, dried and ground to compose a crude ethanolic extract. Food tests were carried out with and without opportunity of choice, using corn leaf discs immersed in the extract at concentrations of 1%, 2% and 4%, for assessment of food consumption (g) and preference index. Later, the extract was topically applied on second- and fifth-instar caterpillars, at concentrations of 1%, 2%, 4% and 6%, in order to observe its effect on survival. In parallel, analysis was conducted to verify the presence and measure the amount of total polyphenols and flavonoids in the extract. There was contact action between the extract and second-instar caterpillars at all concentrations, with treatment 6% causing 100% of mortality 72 hours after application. None of the treatments promoted contact action on fifth-instar caterpillars. In food tests with and without opportunity of choice, all treatments caused reductions in consumption, which classified all as phagodeterrent, with treatment 4% standing out as the least favorite. The presence of total polyphenols and flavonoids was found in the extract, presenting 58.75 ug/mL and 150.1 ug/mL, respectively. The A. curassavica extract proved promising in S. frugiperda control.